Trend analysis of drought in Antalya basin, Türkiye, using classical and innovative approaches - Ercan, Cansu; Abu Arra, Ahmad; Sisman, Eyup (SPRINGER INT PUBL AG, 2025)
Due to the increasingly negative impacts of drought, which affects water resources, agricultural activities, and all sectors, there is a need to analyze the drought trend to understand its effects and mitigate them comprehensively. This research aims to spatiotemporally analyze the drought trend based on the well-known Standardized Precipitation Index (SPI) at different timescales using classical and innovative trend analysis methodologies, including Mann-Kendall (MK), Sen's slope (SS), and newly proposed Frequency Innovative Trend Analysis method (F-ITA) over the Antalya basin, T & uuml;rkiye with monthly precipitation data from 1969 to 2022 for the first time in the literature. Also, the research calculates the slope and actual trends using SS and ITA methodologies along with the drought classifications and frequencies, providing a deeper understanding of the drought patterns and their variability. This research generally indicated an increasing trend in drought events for SPI-3 and SPI-6 based on classical methods and F-ITA graphs for specific stations. However, F-ITA for SPI-12 showed a significant drought trend across all stations, with increased drought frequencies; for example, Alanya station exhibited a monotonic increasing trend, with the frequencies of MD, SD, ED, and EXD approximately doubling over the study period. The spatial distribution of slopes computed by SS and ITA and their respective actual trends exhibited significant parallels, resulting in more frequent drought events and an increased drought trend in the southern parts of the region near the coast. The southern and southeastern parts of the study area exhibited the highest trends and slopes. In summary, analyzing drought trends and their spatio-temporal distribution provides critical and crucial insights for sustainable water resources management and agriculture, and guides policymakers in developing effective adaptation and mitigation strategies.
Keywords: Climate change; Drought assessment; Water resources management; Time series; Frequency-innovative trend analysis (F-ITA); Standardized precipitation index (SPI); SPATIOTEMPORAL ANALYSIS; PRECIPITATION; ECOSYSTEM; TESTS; Geochemistry & Geophysics